FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ISPA DI WILAYAH KERJA PUSKESMAS WENANG KOTA MANADO - Pinontoan, Gabryela Irene; Toar, Jilly; Pajung, Bertom Ch. (Yayasan Syalom Cipta Sumikolah, 2024)
Acute respiratory tract infectious disease (AIDS) remains one of the leading causes of morbidity and mortality of infections in the world. According to the WHO (2021), more than four million people die each year from ISPA. This study aims to examine the relationship between knowledge, attitudes, and behavior to ISPA incidents in the Puskesmas Wenang work area, Manado City. The research methods used are analytical observational with a quantitative approach and cross-sectional design. A total of 127 respondents from the population of 186 respondents participated in the study. The results show that there is a significant correlation between knowledge (p-value = 0.024), attitude (p - value = 0.036), and behavior (p – value = 0.001) with ISPA incidents. Based on the results of this study, it is recommended that the public continue to take ISPA preventive measures proactively, and that the health officers in Puskesmas and the government increase socialization about the prevention of ISPA.